MEMBANGUN DIFERENSIASI PADA RITEL TRADISIONAL - MELISA, . (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The quantity of modern market is increased and ready to replace traditional market. The minus point of traditional market make the market to be forgot by the customer. The added point of modern market, like opening hours, pleasure, and location that make customer like it. Differentiation strategy at traditional market caused internet is visited by consumers. One of the differentiation strategy at traditional market is supply the handmade products which give the high value for consumer. The promotion support can build positive image about the traditional market so the consumer have positive image about the traditional market.